Influence of the Twisting Triangle on Yarn Quality in a Ring Spinning Machine - Sharifhon Alihanov; Husanhon Bobojanov; Alijon Yusupov (Genius Journals, 2023)
This article compares the Uster Statistics 2018 with the 50% indicators of the yarns obtained by changing the flow of fibres coming out of the output cylinders of the spun yarns from the ring spinning machine at different angles.
Keywords: spun thread; angle; linear density